The economic impact of contract farming for smallholders’ tobacco producers in Urambo District, Tabora region - Kassim, Ashura Urassa (Mzumbe University, 2024)
A research report submitted as a partial fulfillment of the requirements for award of the Master of Procurement and Supply chain Management